Ultralow-loss optical diamagnetism in silver nanoforests - Cook, J.J.H.; K. L. Tsakmakidis; Hess, O. (Journal of Optics A: Pure and Applied Optics, 2009)
A comprehensive investigation of the optical properties of a composite metamaterial in which silver nanowires are aligned inside a finite-thickness dielectric host medium is presented. Using a rigorous finite-element based modelling approach, together with a self-consistent process for the extraction of effective-medium parameters, we find that this structure can enable an effective optical diamagnetic response that is orders of magnitude stronger compared to that of naturally occurring diamagnetic materials. Interestingly, our analysis reveals that there is a frequency region where the nanoforest exhibits a strong diamagnetic response while simultaneously allowing for high transmission of incident electromagnetic waves. We examine the physical origin behind the magnetic properties of this structure, as well as its resilience to fabrication imperfections. Our analysis shows that the structure is robust to the presence of disorder, in the occurrence of which it can still facilitate high figure-of-merit diamagnetic responses. © 2009 IOP Publishing Ltd.